Development and the Effectiveness of the Hemomarvel to Understand the Circulatory Blood System among Form 4 Students - Purwadi, Nur Zaidatul Ilma; Abu Bakar, Adibah; Fawaida, Ulya; Saidin, Syazwan (International Journal of Advanced Research in Future Ready Learning and Education, 2025)
Game-based learning has emerged as a powerful pedagogical approach, offering engaging and interactive experiences that enhance students’ understanding and retention of complex concepts. In the context of secondary school biology education, topics such as the circulatory system are often challenging for students to grasp using conventional methods. This study aimed to address this issue by developing HemoMarvel, an educational board game designed to facilitate learning of the circulatory system, and by evaluating its effectiveness in enhancing students’ academic achievement compared to the conventional ‘talk and chalk’ method. The study employed the input–process–output (IPO) model to design and develop HemoMarvel systematically. A quasi-experimental research design was adopted to test its effectiveness. Two groups of students from two different schools participated in the study: an experimental group (n=15), which utilized HemoMarvel, and a control group (n=15), which followed traditional instructional methods. Students’ achievement was assessed through pre-and post-tests, and their scores were analyzed to evaluate the impact of the intervention. Results demonstrated that the mean post-test scores of students in the experimental group were significantly higher than those of the control group, with t (15) = 5.579, p < 0.05. These findings highlight the potential of game-based learning tools like HemoMarvel to foster deeper understanding and improve academic performance. The implications of this study extend to the practice of biology education in schools, providing an alternative teaching and learning tool that enhances comprehension and engagement. By integrating HemoMarvel into the curriculum, educators can address learning challenges in the circulatory system and potentially other complex biology topics. Future research is recommended to explore its scalability, long-term impact, and applicability to other scientific disciplines and educational settings.